Construcción de un reactor fotocatalítico monitoreado por LabVIEW para determinar el ciclo de vida de la ilmenita (2018)
In the present work of degree the conceptual design and construction of a fotocatalítico reactor is realized, for which tests to scale are developed to laboratory with capacity of 25ml, where semiconductor parameters are evaluated like particle size, quantity and disposition inside the reactor; reaching a 96.5% methylene blue removal achieved with 2.5g of unmelted ilmenite contained in disks, in a time of one hour. Subsequently, the photocatalytic reactor is constructed in PVC, with a capacity of 1.2L, monitored and controlled with the LabVIEW engineering software. Said programming is carried out by state machines, obtaining seven states for the reactor, corresponding to: initialization, filling, degradation, emptying, purging, configuration and finally emergency stop. After this, the control system is integrated with the reactor and finally the life cycle of the ilmenite semiconductor contained in discs is determined. Doing a team work of chemical and mechanical engineering to carry out this project in its entirety, obtaining results of removal of methylene blue in the photocatalytic reactor of 91.2% in 2 hours and 10 minutes.